2004
DOI: 10.1021/jm0308850
|View full text |Cite
|
Sign up to set email alerts
|

New Analogues of Amonafide and Elinafide, Containing Aromatic Heterocycles:  Synthesis, Antitumor Activity, Molecular Modeling, and DNA Binding Properties

Abstract: Amonafide- and elinafide-related mono and bisintercalators, modified by the introduction of a pi-excedent furan or thiophene ring fused to the naphthalimide moiety, have been synthesized. These compounds have shown an interesting antitumor profile. The best compound, 9, was 2.5-fold more potent than elinafide against human colon carcinoma cells (HT-29). Molecular dynamic simulations and physicochemical experiments have demonstrated that these compounds are capable of forming stable DNA complexes. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 22 publications
1
59
0
1
Order By: Relevance
“…Peroxide release was detected by measuring the production of oxidized o-dianisidine, which can be detected by its absorbance at 440 nm. According to the manufacturer's instructions, after cells were treated with MNISpd (final concentration: 3, 6, 9, 12 and 16 μM) for 24 h, or treated with 9 μM MNISpd for 12, 24, 36 and 48 h, cells (5x10 6 ) were washed twice with PBS, and then lysed in 500-μl lysis buffer on ice for 30 min. Cell lysates were centrifuged at 16,000 x g for 5 min at 4˚C.…”
Section: Detection Of Reactive Oxygen Species Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxide release was detected by measuring the production of oxidized o-dianisidine, which can be detected by its absorbance at 440 nm. According to the manufacturer's instructions, after cells were treated with MNISpd (final concentration: 3, 6, 9, 12 and 16 μM) for 24 h, or treated with 9 μM MNISpd for 12, 24, 36 and 48 h, cells (5x10 6 ) were washed twice with PBS, and then lysed in 500-μl lysis buffer on ice for 30 min. Cell lysates were centrifuged at 16,000 x g for 5 min at 4˚C.…”
Section: Detection Of Reactive Oxygen Species Levelmentioning
confidence: 99%
“…Many analogues of mononaphthalimide have been designed and synthesized (4), amonafide, one representative mononaphthalimide derivative, has been selected and progressed to clinical treatment (5) but fails to enter phase III. Despite this, a series of analogues of mononaphthalimide have been evaluated in vitro (6,7). UNBS5162, a new analogue of mononaphthalimide, is currently in phase I clinical trial (8).…”
Section: Introductionmentioning
confidence: 99%
“…Others resorted to the combined chemotherapy of amonafide with 1-h-D-arabinofuranosylcytosine, producing efficacy for patients with poor-risk acute myelogenous leukemia (13). More appreciable naphthalimide derivatives with favorable pharmacologic profiles have been encouraged to be designed and synthesized (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The targeted molecular dynamics (tMD) approach has been considered for comparing the relative energetic cost involved in creating the intercalation sites and also studying the mechanisms of action [Braña et al, 2004]. It has been found that the electrostatic contribution is a critical characteristic of binding selectivity [Marco et al, 2005].…”
Section: Interaction Of Molecules With Dnamentioning
confidence: 99%